Distinctive Feature of Risk in Health Care Organizations - MOHAMMED, KASSIM (IJRDO - Journal of Social Science and Humanities Research, 2019)
Risk is present in all types of organizations and is perceived as one of the main features of human daily life, as there is no single outcome that is absolutely certain. Risk management has become a crucial part of any effective management system. However, risk in Health Care Organizations (HCOs) has some distinctive attributes that make it unique and an indispensable obligation. This descriptive study, which is based on examining, elaborating, illustrating, and tackling related researches and literature in risk in healthcare and uses a systematic literature review technique, aimed at discussing and addressing the main characteristics and traits that distinguish risk in the healthcare sector and HCOs from risk in other sectors and organizations. As a result, the study highlighted seven distinctive features of risk that relate closely to the healthcare sector and HCOs.